Immunohistochemical Analysis of Breast Cancer at BP Koirala Memorial Cancer Hospital Nepal - Pun Magar, Chin Bahadur; Pandey, Greta; Uprety, Suraj; Dhungana, Ishan; Jha, Nandita (Nepalese Journal of Cancer, 2023)
Introduction: Immunohistochemistry test is used to characterize intracellular proteins or various cell surfaces in all tissues. It is used to solve diagnostic problems or for determining prognosis and response to therapy in breast pathology. ER, PR and HER2 are well established biomarkers for breast cancer prognosis and for guiding treatment. Materials and methods: This is retrospective study at Department of Pathology of B P Koirala Memorial Cancer Hospital in Bharatpur, Chitwan, Nepal effective from 15 April 2020 to 14 April 2021. All the data were retrieved and analyzed. Results: Total 205 breast cancer cases were analyzed, among them 198 cases were females accounting 96.5 % and 7 cases were males accounting 3.5 %. Altogether 125 (60.9%) cases had immunohistochemistry panel of ER, PR and HER2 tests done. 48% cases were ER positive, 42.4% cases were PR positive, 34.4% were HER2 positive and 9.9% cases were triple negative. Conclusion: Breast cancer is more common in females than in males. Most common affected age group was 41-50 years. Most common histological type was invasive ductal carcinoma NST. In order to improve breast cancer outcomes and survival, early diagnosis, immunohistochemistry hormone analysis and screening tests should be done.